ADHD and Psychoactive Substance Abuse - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The effect of attention-deficit hyperactivity disorder (ADHD) compared to psychiatric comorbidity, familiality, and adversity, as risk factors for psychoactive substance use disorder (PSUD) was evaluated at the Department of Psychiatry, Massachusetts General Hospital, Boston, MA.